Digital educative public message: Health protocol awareness at pandemic COVID-19 periods (Instagram feeds @humasprovjatim) - Jokhanan Kristiyono; Delmarrich Bilga Ayu Permatasari; Julyanto Ekantoro; Fitria Widiyani Roosinda (Masyarakat, Kebudayaan dan Politik, 2022)
Dissemination of information related to the issues of the COVID-19 pandemic on the Instagram account @humasprovjatim is interesting to study because of understanding the meaning and motives behind educational messages conveyed through the Instagram account @humasprovjatim. It can form awareness regarding health protocols during the pandemic and post-COVID-19 pandemic to realize changes in attitudes, behavior, and healthy lifestyles that reduce the spread of COVID-19. This study aims to analyze educational messages aware of health protocols on the Instagram account of Public Relations (PR) of East Java Province (@humasprovjatim). This study used content analysis methods with Pentad’s Dramatic Analysis. The object studied was educational messages from the PR Instagram feed in March-December 2020. Result of this research is the dramatic rhetoric in the content of the Instagram feed by the PR of the province of East Java. The Instagram media is a rhetorical stage in conveying the message of community life in dealing with COVID-19. Conclusion of this research is that there is an important role for packaging content on their Instagram. The results of this study explain that the PR Instagram account is a stage where a "show" occurs which is considered capable of bridging the government to build educational messages regarding the health protocols presented in such a way to the public.